2015 Physics Education Research Conference Proceedings 2015
DOI: 10.1119/perc.2015.pr.073
|View full text |Cite
|
Sign up to set email alerts
|

Student difficulties with complex numbers

Abstract: Complex numbers and functions are used in multiple subfields in undergraduate physics. We use pretests, quizzes, and exams administered throughout the junior year to identify middle-division students' difficulties with complex number fluency. These difficulties are classified into three categories: performing calculations, switching between forms, and appropriately selecting forms to simplify calculations. Our exploration suggests that students in middle-division physics courses have varying levels of fluency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
5
0
2
Order By: Relevance
“…About 35% (N ¼ 83) gave correct numerical results for both modulus squared, and 17% made errors in computing j 3 5 þ i 4 5 j 2 . The most salient error appears to be treating modulus squared (e.g., j 3 5 þ i 4 5 j 2 ) as squared [e.g., ð 3 5 þ i 4 5 Þ 2 ], which has been documented in prior research [35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…About 35% (N ¼ 83) gave correct numerical results for both modulus squared, and 17% made errors in computing j 3 5 þ i 4 5 j 2 . The most salient error appears to be treating modulus squared (e.g., j 3 5 þ i 4 5 j 2 ) as squared [e.g., ð 3 5 þ i 4 5 Þ 2 ], which has been documented in prior research [35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…Even simple arithmetic involving complex numbers has been found to be difficult for undergraduates. 48,49 On the other hand, Wawro et al 50 have published promising research showing student abilities to critique and understand the purposes of linear algebra and Dirac notations in quantum mechanics and demonstrated students flexibility in reasoning about linear algebra and quantum concepts; this indicates that students should be cognitively able to work with abstract operator algebra.…”
Section: Physics Education Knowledge Base For Teaching Quantum Mechanicsmentioning
confidence: 99%
“…Many undergraduate engineering students' mathematical content knowledge and arithmetic skills of complex number-related topics often fall short. Furthermore, many studies at various educational levels reveal that students need help with conceptual and procedural knowledge of complex numbers (Ahmad & Shahrill, 2012;Conner et al, 2007;Smith et al, 2015). A study by Hui and Lam (2013) revealed that many students need clarification on geometrical and algebraic representations of complex numbers.…”
Section: Introductionmentioning
confidence: 99%